2013
DOI: 10.1152/ajpregu.00225.2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced contractility in pregnancy is associated with augmented TRPC3, L-type, and T-type voltage-dependent calcium channel function in rat uterine radial artery

Abstract: In pregnancy, ␣-adrenoceptor-mediated vasoconstriction is augmented in uterine radial arteries and is accompanied by underlying changes in smooth muscle (SM) Ca 2ϩ activity. This study aims to determine the Ca 2ϩ entry channels associated with altered vasoconstriction in pregnancy, with the hypothesis that augmented vasoconstriction involves transient receptor potential canonical type-3 (TRPC3) and L-and T-type voltage-dependent Ca 2ϩ channels. Immunohistochemistry showed TRPC3, L-type Ca v1.2 (as the ␣1C subu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
(94 reference statements)
2
13
0
Order By: Relevance
“…TRPCs as a subfamily of calcium channels have been increasingly concerned [13]. Senadheera et al found that increased TRPC3 can enhance the contractility of a pregnant uterus [6]. Their findings indicate that TRPC3 is likely a factor involved in the initiation of labor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPCs as a subfamily of calcium channels have been increasingly concerned [13]. Senadheera et al found that increased TRPC3 can enhance the contractility of a pregnant uterus [6]. Their findings indicate that TRPC3 is likely a factor involved in the initiation of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential channels (TRPC) are a group of nonselective cation channels with six transmembrane spanning helices [5, 6]. Activation of TRPC leads to trans-sarcolemmal Ca 2+ influx to directly increase the intracellular Ca 2+ concentration; it can also lead to trans-sarcolemmal Na + influx to indirectly increase the intracellular Ca 2+ concentration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Incremental doses of 0.01 nmol/L to 1mmol/L bradykinin (Auspep, West Melbourne, Australia) were infused, and vasodilation was assessed with video microscopy (Diamtrak Software, Adelaide, SA, Australia). 72 Assessment of the effect of metformin on angiogenesis with the use of omental artery explants Omental artery explants (0.5-mm rings) were stained with calcein AM (Merck Millipore, Darmstadt, Germany) and imaged at Â40 magnification with the EVOS FL microscope (Life Technologies); outgrowth was assessed with image J (http://imagej.nih.gov/ij/). 73…”
Section: Assessment Of the Effect Of Metformin On Whole Omental Artermentioning
confidence: 99%
“…Furthermore, 13 novel upregulated genes (10-13 fold) including Esm1, Slfn4, Usp18 and Grem1 and 4 downregulated genes (4-7 fold), including S100g, Pcp4, Col6a4, and Trpc3 were identified in the pregnant UA. While many of these genes were associated with gestational pathologies [34][35][36][37][38][39], the differential expression of these genes in healthy pregnancy relative to non-pregnancy suggests that these genes may have a unique role in gestational uterine vascular adaptations.…”
Section: Discussionmentioning
confidence: 99%